Dose-and time dependent effects of oil-palm (Elaeis guineensis) leaf extract in streptozocin-induced oxidative stress and renal damage in diabetic rats / Varatharajan Rajavel - Vatharajan, Rajavel (2016)
Diabetic nephropathy is a major microvascular complication of diabetes and is the leading cause of end-stage renal disease. Treatment with antioxidants produced marginal benefit in preventing diabetic renal complications. Human studies showed that high dose of vitamin E failed to impart beneficial effect. The outcomes of these studies thus lay emphasis on the significance of developing better novel antioxidant treatments for reducing diabetic nephropathy. Oil palm (Elaeis guineensis) leaves are underutilized in tropical countries including Malaysia, and the ethanol extract of oil palm leaves (OPLE) is rich in flavonoids and catechins. The present study aimed to investigate the effectiveness of OPLE in attenuating hyperglycaemia-mediated oxidative stress and renal dysfunction in streptozotocin-induced diabetic rats. Sprague-Dawley rats received OPLE at a dose of 200, 500 or 1000 mg/kg/day for 4 or 12 weeks after diabetes induction with streptozotocin (60 mg/kg, i.p.). At the end of 4 or 12 weeks, blood glucose level, body and kidney weight ratio, urine flow rate (UFR), glomerular filtration rate (GFR), fractional sodium (FNa+ ) and absolute potassium (K+ ) excretions, urinary 8-hydroxy-2-deoxy guanosine (8-OHdG) and proteinuria were assessed. Glutathione (GSH), lipid peroxides (LPO), western blotting assay and immunohistochemistry staining for nicotinamide adenine dinucleotide phosphate (NADPH) oxidase p22-phox and p67-phox subunits, and morphology were analysed in renal tissue while transforming growth factor- beta1 (TGF-β1) was measured in plasma. Significant increase in blood glucose, decreased body weight and increased kidney weight to body weight ratio were observed in diabetic rats. Proteinuria, UFR, GFR, FNa+ and K + excretions were increased. Concomitant iv with these alterations, an increase in LPO and a decrease in GSH in renal tissues were observed while urinary 8-OHdG and plasma TGF-β1 were elevated. Histological evaluation demonstrated glomerulosclerosis and tubulointerstitial fibrosis. Consistent with these reports, NADPH oxidase p22phox and p67phox subunits were enhanced as evaluated by western blotting and immunohistochemistry in rats with 4 and 12 weeks diabetes, respectively. OPLE at all tested doses (200, 500 and 1000) mg/kg/day prevented these changes and preserved renal architecture in the 4-week study. In contrast, only 500 mg/kg/day of OPLE in the 12-week study exhibited a significant improvement in the renal functional changes and morphology, concurrently with improvement in the oxidative stress biomarkers, plasma TGF-β1, and the NADPH oxidase p22phox and p67phox subunits. OPLE 200 mg/kg/day in the 12-week study exhibited improvements only with respect to renal blood flow, protein and K+ excretions, and NADPH oxidase p22phox and p67phox subunits. Paradoxically, 1000 mg/kg/day of OPLE in the 12-week study exhibited no significant improvement in the above parameters; renal injury was aggravated due to prooxidant action. Proteinuria, UFR, GFR, FNa+ and K + excretions were increased. Concomitant with these alterations, renal LPO was increased and renal GSH was decreased whilst urinary 8-OHdG and plasma TGF-β1 were elevated. Histological evaluation demonstrated glomerulosclerosis and tubulointerstitial fibrosis. Consistent with these results, immunohistochemistry and western blotting assay demonstrated an increased in the NADPH oxidase p22phox and p67phox subunits. These results indicate the pro-oxidant action of OPLE at high dose (1000 mg/kg/day) when administered for longer duration (12 weeks).